Betrayal of Trust in Medical Manslaughter. (December 2019) - Wheeler, Rupert; Wheeler, Robert
Despite efforts spanning 200 years, judges are yet to find a form of words that can explain adequately the meaning of 'gross' to a jury trying gross negligence medical manslaughter. Accordingly, those assessing whether to prosecute the crime are equally bewildered unable to calculate the likelihood of conviction. Jurors tasked with determining a defendant's guilt are faced with a lack of clarity that often fails to render just results. We are led to conclude that an entirely different formula is required for assessing whether a defendant is guilty of manslaughter in the medical context. We propose that, rather than requiring the prosecution to prove that the defendant's actions were truly, exceptionally bad (as currently required for gross negligence manslaughter), a more appropriate test would be whether there has been a betrayal of trust by the doctor towards his patient, resulting in death. This is akin to breaching a fiduciary duty. Through applying the test to the facts of well-known cases, we argue that the 'betrayal of trust' test would be easier for juries, defendants and practitioners to understand. Furthermore, the proposed test avoids the long-standing difficulty of circularity that exists in the current law and is able to separate more effectively the distinction between a doctor's personal failings and the failings of the system. We conclude that though the 'betrayal of trust' test may result in fewer prosecutions, the corresponding impact on the medical profession would ultimately be beneficial to society.